Investigating the Effect of SARS-CoV-2 upon the Anti-Viral and Immune Responses of Human Polymorphonuclear Leukocytes (PMNs) - Alotaibi, Abdulaziz Najem (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2026)
Human polymorphonuclear leukocytes (neutrophils) are critical innate immune cells that deploy antimicrobial and pro-inflammatory mechanisms, including reactive oxygen species (ROS) generation, cytokine secretion, degranulation, Neutrophil Extracellular Traps (NETs), and phagocytosis. While their functions against bacteria and fungi are well defined, their roles in viral infections are less clear. Severe Coronavirus disease 2019 (COVID-19) displays an atypical immune profile for a viral infection, marked by lymphopenia and neutrophilia, with disease severity closely associated with an elevated neutrophil-to-lymphocyte ratio. Massive neutrophil infiltration into the lungs is a hallmark of critical disease, yet the molecular pathways by which neutrophils sense Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and shape inflammation remain incompletely understood. Therefore, this study addressed three aims: (1) to assess the effects of purified SARS-CoV-2 spike protein (SP) on neutrophil activation, effector functions, and cytokine release; (2) to determine whether GU-rich viral single-stranded RNA (ssRNA) activates neutrophils via Toll-like receptor 8 (TLR8) and to characterize the downstream inflammatory responses; and (3) to compare neutrophil responses to direct infection with live SARS-CoV-2 (Delta variant) versus indirect stimulation by soluble mediators from infected lung epithelial cells. A combination of flow cytometry, functional assays, ELISA, qRT-PCR, and Western blotting was employed to assess neutrophil phenotypes, effector responses, cytokine production, and intracellular signalling pathways. Distinct responses emerged depending on the viral component encountered. The SARS-CoV-2 SP did not induce classical neutrophil activation, as shown by the absence of CD66b and CD11b upregulation, CD16 and CD62L downregulation, ROS production, or degranulation. Instead, SARS-CoV-2 SP selectively triggered IL-8 secretion via TLR2/4, promoted TGF- release through integrin-dependent signalling, suppressed NET formation, and prolonged neutrophil survival. In contrast, GU-rich viral ssRNA elicited robust inflammatory activation through TLR8, driving CD11b upregulation, Nuclear Factor kappa-light-chain-enhancer of activated B cells (NF-B) signalling, and strong secretion of TNF-, IL-6, IL-1, and IL-8. These responses were abolished entirely by TLR8 inhibition. Direct infection with the Delta variant produced a distinct phenotype, downregulating CD11b while upregulating CD63 (a degranulation marker), inducing potent TLR8-dependent IL-1 release, and activating antiviral PKR and STAT1 pathways. Finally, epithelial-cell-derived supernatants induced only modest and variable effects: Delta supernatants reduced ROS production, IC-19 supernatants enhanced neutrophil elastase release, and other viral strains showed little activity. This study demonstrates that SARS-CoV-2 can modulate neutrophil function through distinct mechanisms, including selective anti-inflammatory responses to SP, TLR8-mediated inflammation triggered by ssRNA, and IL-1-driven inflammation following live virus infection. The findings indicate that neutrophils respond differently to individual viral components via distinct molecular pathways, which may help explain aspects of neutrophil dysfunction during COVID-19 and highlighting potential therapeutic targets for managing viral inflammatory responses while preserving beneficial immune functions.
APPROVED
Keywords: SARS-CoV-2; COVID-19; Neutrophils; Polymorphonuclear leukocytes (PMNs); Innate immunity; Antiviral immune response; Toll-like receptor 8 (TLR8); TLR2/TLR4 signalling; NF-B signalling; MAPK pathway; Interferon-stimulated genes (ISGs); NETosis; Reactive oxygen species (ROS); Apoptosis and cell survival; Neutrophil activation